Emotional Performance as Work Skill: Low‐Income Women in Israel Learning to Talk the Talk. (June 2016) - Sa'ar, Amalia
Abstract: This article documents the use of emotion pedagogies (EP) during economic empowerment projects for low‐income Hebrew‐speaking women in Israel, where a significant part of business‐training curriculum is dedicated to narratives of self and performances of reflexive, emotional speech. Participant observations in weekly training sessions reveal contradictory effects: Despite clear neoliberal undertones of self‐reliance, individual responsibility, and depoliticizing women's economic vulnerability, participants actually enjoy the opportunity to talk about their emotions and are particularly inclined to describe their work using the words "love, " "care, " and "giving." From their perspective, EP yields some important benefits even if their income remains low: The workshops give them an opportunity to acquire middle‐class emotional competence, to exercise community, to undergo personal growth, and more. Exploring the various layers of signification that emotion pedagogies assume on the ground reveals a multivocal vernacular version that combines globally circulating ideas and locally specific discourses.